2013
DOI: 10.1061/(asce)ee.1943-7870.0000698
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Maintenance Cost, Labor Demands, and System Performance for LID and Conventional Stormwater Management

Abstract: The perception of the maintenance demands of low impact development (LID) systems represents a significant barrier to the acceptance of LID technologies. Despite the increasing use of LID over the past two decades, stormwater managers still have minimal documentation in regard to the frequency, intensity, and costs associated with LID operations and maintenance. Due to increasing requirements for more effective treatment of runoff and the proliferation of total maximum daily load (TMDL) requirements, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 5 publications
0
49
0
Order By: Relevance
“…In Hong Kong, the annualized O&M costs are expressed as a percentage of the capital costs -4% for porous pavement and 8% for bioretention (Houle et al, 2013). The O&M costs of green roof are extracted from Townshend and Duggie (2007 Table 3 presents some example O&M activities.…”
Section: Oandm Costmentioning
confidence: 99%
“…In Hong Kong, the annualized O&M costs are expressed as a percentage of the capital costs -4% for porous pavement and 8% for bioretention (Houle et al, 2013). The O&M costs of green roof are extracted from Townshend and Duggie (2007 Table 3 presents some example O&M activities.…”
Section: Oandm Costmentioning
confidence: 99%
“…Since maintenance requirements for bioretention practices are still being established [30], costs will then very substantially based upon what activities are conducted. In a recent study, Houle et al [142] provided insight into maintenance activities by tracking costs and labor demands for bioretention practices over a period of 2-4 years. The authors found that despite conventional wisdom, LID practices such as bioretention, which typically require proactive rather than reactive maintenance, experience lower marginal costs than conventional practices.…”
Section: Costsmentioning
confidence: 99%
“…Nonpoint sources of nitrogen, due to their diffuse nature, are more challenging to address on an ecosystem scale. Typically, runoff from agricultural fields and stormwater are two of the major focus areas of management plans for reducing nonpoint sources of nitrogen (Collins et al, 2010;Houle et al, 2013;Passeport et al, 2013).…”
Section: Introductionmentioning
confidence: 99%